Evaluating correlates of healthy eating and dietary quality among older adults: a mixed methods approach to development and application of a new survey instrument - Rosenkranz, Sara K.; Shahamati, Donya; Biggins, Anna; Mick, Alissa; Acosta, Christopher; Rosenkranz, Richard R. (Frontiers in Public Health, 2025)
ObjectivesCommunity-dwelling older adults face unique challenges related to nutrition and health, but little is known about their barriers and facilitators for healthy eating behaviors. This study sought to develop and evaluate a new instrument to measure the capability, opportunity, and motivation for healthy eating behaviors (COM-HE) among community-dwelling older adults.DesignA mixed methods approach was used to obtain qualitative and quantitative data. Participants were aged 65 years or older, community-dwelling, and English-speaking. Participants engaged in focus groups (n = 12) and pilot-testing (n = 81) to evaluate the COM-HE instrument. The Rapid Eating Assessment for Participants – Shortened Version (REAP-S) questionnaire was utilized to examine correlations between the COM-HE instrument and self-reported dietary quality. Descriptive and inferential statistics were used to investigate acceptability, reliability, and validity.ResultsThe COM-HE instrument achieved acceptable internal consistency (Cronbach’s alpha = 0.847–0.986), displayed varying levels of uni-dimensionality based on multiple principal component analyses (total variance explained by three components = 86.72%), and was correlated with self-reported dietary quality scores (r = 0.409, adjusted R2 = 0.099, p = 0.031). Preliminary data suggest that the scale was acceptable in terms of readability and understanding among a convenience sample of generally well-educated older adults.ConclusionThe new COM-HE instrument was acceptable, reliable, and valid among a homogeneous sample of adults over 65 years of age. These results suggest a need for additional development, evaluation, and refinement of the instrument in more diverse groups of older adults.